Digital Flipbook: An Innovative Medium for Arabic Vocabulary Learning - Farida; Faiqoh, Putri Kholida; Faruq, Umar (Proceeding International Conference on Education, 2025)
This research is based on issue in Arabic language learning at MTsN 1 Kediri, especially the lack of use of technology in developing materials from UKBM books. Students get bored quickly and have difficulty understanding the material, while they are more enthusiastic when learning with digital media. The main focus of Arabic language learning is mastery of vocabulary, so researchers develop learning media in the form of flipbook-based digital books to support mastery of vocabulary. This book is designed according to students who are familiar with technology. The purpose of this study was to determine the development process and effectiveness of using flipbook digital books in learning Arabic vocabulary at MTsN 1 Kediri. This study uses the R&D method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation by media and material experts obtained an average of 92.31% from media experts and 90% from material experts which is included in the very feasible category. The effectiveness of the media was tested using the N-Gain test, with an average result of 0.76 is include in the high category and effective, indicating a significant increase in mastery of vocabulary after using flipbook digital books.